Analysis of the operational status of the three-level referral system for urologic ultrasound screening and risk factors for renal pelvic dilatation in high-risk children - Ji, Baowei; Gong, Yinv; Zhang, Ying; Li, Yun; Zhai, Yihui; Sun, Yinghua; Wang, Xiang; Jia, Lishan; Xu, Hong; Shen, Qian (Frontiers in Pediatrics, 2023)
Background Congenital Anomalies of the Kidney and Urinary Tract (CAKUT) are the primary cause of end-stage renal disease in children, early diagnosis and treatment can significantly improve the kidney function. Among CAKUT, renal pelvis dilatation (RPD) due to various causes has the highest detection rate, which can be detected early by postnatal ultrasound screening. Since 2010, the Children's Hospital of Fudan University (CHFU), together with the Minhang District Maternal and Child Health Hospital (MCH) and Community Health Centres (CHCs) of Minhang District has created a three-level referral system for urological ultrasound screening. This study aims to describe the operation of a three-level referral system for ultrasound screening of CAKUT and to select risk factors of RPD in high-risk children. Methods The operation of the three-level referral system was assessed by analyzing the screening volume, screening rate, referral rate, and follow-up rate; risk factors of RPD in high-risk children were selected by chi-square test and multivariate logistic regression. Results A total of 16,468 high-risk children were screened in ten years, and the screening volume was maintained at about 1,500 cases per year; the screening rate showed a linear increase, from 36.8% in 2010 to 98.2% in 2019; the referral rate from the CHCs to the MCH was 89.9% significantly higher after 2015 than that of 84.7% from 2010 to 2015; the follow-up rate after 2015 was 71.0% significantly higher than that of 46.3% from 2010 to 2015. Multivariate logistic regression analysis showed that the risk of RPD was 1.966 times higher in males than in females, and the risk of moderate to severe RPD was 2.570 times higher in males than in females; the risk of RPD in preterm children was 1.228 times higher than that of full-term children; and the risk of RPD was 1.218 times higher in twins than in singles. Conclusions The screening volume of the three-level referral system has remained stable over a decade, with significantly higher screening, referral, and follow-up rates. Males, preterm, and twins are risk factors of RPD in high-risk children; males are also risk factors for moderate to severe RPD in high-risk children